Psychological impact of covid-19 on university students using open distance learning / Rafizah Kechil, Nor Hanim Abd Rahman and Noor 'Aina Abdul Razak - Kechil, Rafizah; Abd Rahman, Nor Hanim; Abdul Razak, Noor 'Aina (Unit Penerbitan JSKM, 2021)
During the COVID-19 pandemic, the majority of universities adopted remote learning, also known as open and distance learning (ODL). Various challenges and issues that lecturers and students have to deal with in order to ensure the success of this ODL so that students do not drop out of their courses. The psychological effect of university students during the COVID-19 pandemic is examined in this article. An online survey of 191 university students was used to compile the study. We developed a tool that called Psychosomatic Symptoms Questionnaire (PSQ) using the adopted COVID-19's e-Learning Digital Tools questionnaire and Patient Health Questionnaire- 4 (PHQ-4), the psychological impact of university and school students was determined. The findings show that all students were classified as having moderate depression and anxiety during the COVID-19 pandemic.